2012
DOI: 10.5194/nhess-12-785-2012
|View full text |Cite
|
Sign up to set email alerts
|

A high resolution climatology of precipitation and deep convection over the Mediterranean region from operational satellite microwave data: development and application to the evaluation of model uncertainties

Abstract: Abstract.A new precipitation and convection dataset for the Mediterranean Basin, derived from operational satellite microwave data is documented. The dataset is derived from diagnostics that rely on brightness temperatures measured since 1999 in the water vapour absorption line (183)(184)(185)(186)(187)(188)(189)(190)(191). The dataset consists of twice-daily (a.m. and p.m.) and monthly maps of precipitation and convection occurrences on a 0.2 • lat × 0.2 • long grid for the area 25 • -60 • N, 10 • W-50 • E. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…• The downscaled ERA-interim reanalyses (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) by WRF RCM is named CTL hereafter and has been evaluated in-depth over the land surrounding the Mediterranean Sea (Claud et al 2012;Flaounas et al 2013;Stéfanon et al 2014). The CTL simulations is forced by the ERA-interim SST at its lower boundary over the Mediterranean Sea.…”
Section: Simulationsmentioning
confidence: 99%
“…• The downscaled ERA-interim reanalyses (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) by WRF RCM is named CTL hereafter and has been evaluated in-depth over the land surrounding the Mediterranean Sea (Claud et al 2012;Flaounas et al 2013;Stéfanon et al 2014). The CTL simulations is forced by the ERA-interim SST at its lower boundary over the Mediterranean Sea.…”
Section: Simulationsmentioning
confidence: 99%
“…Since this dataset has been described in details in a recent paper [17], we recall here only the most important points. This study mainly uses the AMSU-B sensor, which is a cross-scanning microwave instrument flying on board NOAA sun-synchronous polar-orbiting satellites since late 1998.…”
Section: Amsu-based Precipitation and Convection Occurrencementioning
confidence: 99%
“…In case of overlapping areas (which occur mostly in the northern part of the area), we interpolate the brightness temperatures of the different orbits. Table 1 summarizes the time intervals considered for each platform (NOAA 15,16,17).…”
Section: Amsu-based Precipitation and Convection Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Some of these regions coincide with areas characterized as being vulnerable to heavy precipitation that induces floods over the MR (Harats et al, 2010). Claud et al (2012) and Alhammoud et al (2014) have extended the data set using measurements from the AMSU-B and the Microwave Humidity Sensor instruments onboard additional NOAA satellites. They found that interannual variability of deep convection is strongest along the northern coasts of the MB.…”
Section: Spatial Distribution Of Deep Convective Precipitation Over Tmentioning
confidence: 99%